Cell-based meat: The molecular aspect - Azhar, Asim; Zeyaullah, Md.; Bhunia, Shushruta; Kacham, Santhosh; Patil, Girish; Muzammil, Khursheed; Khan, Mohammad Suhail; Sharma, Sandeep (Frontiers in Food Science and Technology, 2023)
Cellular agriculture is one of the evolving fields of translational biotechnology. The emerging science aims to improve the issues related to sustainable food products and food security, reduce greenhouse gas emissions and provide animal wellbeing by circumventing livestock farming through cell-based meat (CBM) production. CBM exploits cell culture techniques and biomanufacturing methods by manipulating mammalian, avian, and fish cell lines. The cell-based products ought to successfully meet the demand for nutritional protein products for human consumption and pet animals. However, substantial advancement and modification are required for manufacturing CBM and related products in terms of cost, palatability, consumer acceptance, and safety. In order to achieve high-quality CBM and its production with high yield, the molecular aspect needs a thorough inspection to achieve good laboratory practices for commercial production. The current review discusses various aspects of molecular biology involved in establishing cell lines, myogenesis, regulation, scaffold, and bioreactor-related approaches to achieve the target of CBM.